Elimination of Waste in the Development of Learning Media for Deaf Students Using a Lean Software Development Approach - Aisyah Ayu Mustikasari; Munawir Yusuf; Triana Rejekiningsih (AL-ISHLAH: Jurnal Pendidikan, 2023)
Deafness is a condition where a student cannot hear various sounds optimally. So in the learning process, we need media that prioritizes visuals to make it easier for deaf students to understand the material presented by the teacher. Gamification is one of the most effective learning media because it can present material packaged in the form of game software. The aim of the research is to assist developers in developing gamification by eliminating waste using a lean software development approach. This research method uses the lean assessment matrix method by making process flow diagrams and lean assessment matrices to identify the presence of critical waste. The results showed that the development of deaf students' learning methods used the Lean Software development approach: the number of motions in one game, the game entry process was quite long, and the Latin font was not installed in the application. By eliminating these three wastes, other wastes will be indirectly eliminated because there is a link between the wastes. After the Lean Assessment Matrix process was completed, several solutions were obtained to eliminate this critical waste: making a Future Process Model carefully before giving it to the Developer and making a careful gamification development schedule. By implementing the two Garbage Elimination Alternatives, gamification development can run effectively and efficiently